2018
DOI: 10.1002/stem.2795
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mesenchymal Stem Cells from Human Induced Pluripotent Stem Cells Results in Downregulation of c-Myc and DNA Replication Pathways with Immunomodulation Toward CD4 and CD8 Cells

Abstract: Multilineage tissue-source mesenchymal stem cells (MSCs) possess strong immunomodulatory properties and are excellent therapeutic agents, but require constant isolation from donors to combat replicative senescence. The differentiation of human induced pluripotent stem cells (iPSCs) into MSCs offers a renewable source of MSCs; however, reports on their immunomodulatory capacity have been discrepant. Using MSCs differentiated from iPSCs reprogrammed using diverse cell types and protocols, and in comparison to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 76 publications
(116 reference statements)
1
36
0
1
Order By: Relevance
“…Mechanistically, this effect is mediated through diminished UPR activation, downregulation of Bip , chop , inflammatory genes Il6 , chemokines Cxcl1 and Cxcl2 , and pro‐apoptotic signals ( Bax/Bcl2 ratio) with reversal of Bcl2 gene expression, decreased activation of NF‐κB, JNK kinase and TUNEL‐positive renal cells. Our finding of equivalent efficacy between iPS‐MSCs and BM‐MSCs in ameliorating HFD‐induced kidney injury is in agreement with that observed in other disease models .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mechanistically, this effect is mediated through diminished UPR activation, downregulation of Bip , chop , inflammatory genes Il6 , chemokines Cxcl1 and Cxcl2 , and pro‐apoptotic signals ( Bax/Bcl2 ratio) with reversal of Bcl2 gene expression, decreased activation of NF‐κB, JNK kinase and TUNEL‐positive renal cells. Our finding of equivalent efficacy between iPS‐MSCs and BM‐MSCs in ameliorating HFD‐induced kidney injury is in agreement with that observed in other disease models .…”
Section: Discussionsupporting
confidence: 92%
“…Pharmacological attempts targeting ER stress are still premature . iPS‐MSCs may be a superior alternative to BM‐MSCs for MSC‐based therapy . Here, we showed that both iPS‐MSCs and BM‐MSCs partially reversed renal pathology and albuminuria through suppression of renal ER stress induced by lipotoxicity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Various conditions including ageing, long‐term culture and H 2 O 2 , adverse oxygen content, high glucose, proinflammatory cytokines and other toxic factors, abnormally up‐regulated ROS production can harm MSC activities . On the other hand, although MSCs play critical roles on immunomodulatory properties for therapy in various diseases, the constant isolation from donors also bring out unrecoverable injury …”
Section: Introductionmentioning
confidence: 99%
“…22,[29][30][31][32][33] On the other hand, although MSCs play critical roles on immunomodulatory properties for therapy in various diseases, the constant isolation from donors also bring out unrecoverable injury. 34…”
mentioning
confidence: 99%